Blood pressure levels and risk of haemorrhagic stroke in patients with atrial fibrillation and oral anticoagulants: results from The Swedish Primary Care Cardiovascular Database of Skaraborg. Issue 8 (August 2021) - Bager, Johan-Emil; Hjerpe, Per; Schiöler, Linus; Bengtsson Boström, Kristina; Kahan, Thomas; Ödesjö, Helena; Jood, Katarina; Hasselström, Jan; Ljungman, Charlotta; Manhem, Karin; Mourtzinis, Georgios
Abstract : Objective: To assess the risk of haemorrhagic stroke at different baseline SBP levels in a primary care population with hypertension, atrial fibrillation and newly initiated oral anticoagulants (OACs). Methods: We identified 3972 patients with hypertension, atrial fibrillation and newly initiated OAC in The Swedish Primary Care Cardiovascular Database of Skaraborg. Patients were followed from 1 January 2006 until a first event of haemorrhagic stroke, death, cessation of OAC or 31 December 2016. We analysed the association between continuous SBP and haemorrhagic stroke with a multivariable Cox regression model and plotted the hazard ratio as a function of SBP with a restricted cubic spline with 130 mmHg as reference. Results: There were 40 cases of haemorrhagic stroke during follow-up. Baseline SBP in the 145–180 mmHg range was associated with a more than doubled risk of haemorrhagic stroke, compared with a SBP of 130 mmHg. Conclusion: In this cohort of primary care patients with hypertension and atrial fibrillation, we found that baseline SBP in the 145–180 mmHg range, prior to initiation of OAC, was associated with a more than doubled risk of haemorrhagic stroke, as compared with an SBP of 130 mmHg. This suggests that lowering SBP to below 145 mmHg, prior to initiation of OAC, may decrease the risk of haemorrhagic stroke in patients with hypertension and atrial fibrillation. Abstract : Supplemental Digital Content is available in the text